Speech Delivered at the International Labour Organization, Geneva - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank, shared his vision of trying to support an inclusive and sustainable globalization. He explained the World Bank Group’s six strategic directions: (i) Assisting the poorest countries, especially in Sub-Saharan Africa, to develop and grow; (ii) Addressing the post-conflict states and states facing breakdown; (iii) Integration of China , India , and the other middle-income countries in the international economic system; (iv) Address the global public goods agenda, such as global climate change and the environment, health issues that cross borders, Aid-for-Trade so that countries can take better advantage of open markets, and financial systems for development and stability; (v) Fostering development and opportunity in the Arab world; and (vi) Pursuing the agenda of knowledge and learning. He shared policy guidelines to help pursue policies to help all workers, through building skills, adapting to change, and paying attention on the special challenges of girls and women. Areas of cooperation include: hunger and malnutrition; the Better Work Initiative; the Youth Employment Network; child labor; migration; and microfinance.